(untitled) (Colombia Medica, 2022)
Introduction Triphasic waves (TW) constitute an electroencephalographic pattern associated with certain kinds of encephalopathy. In addition, brain atrophy may be a predisposing factor linked with triphasic waves. Objective To compare the degree of brain atrophy and white matter disease between patients with acute encephalopathy with and without triphasic waves. Methods A retrospective observational study included adult patients with encephalopathy, with and without triphasic waves, hospitalized between 2016 and 2017. The degree of brain atrophy and white matter lesion were defined using the Global Cortical Atrophy and Age-Related White Matter Changes (ARWMC) scales, respectively. Scores were compared between groups. Mortality rates were registered. Results Sixteen patients with triphasic waves were identified matched by age and sex with 30 patients without triphasic waves. The mean age was 80 years in the triphasic waves group. Women represented 87.5%. Multifactorial encephalopathy was the most frequent diagnosis, followed by metabolic encephalopathy. Patients with triphasic waves had more brain atrophy (10.43 vs. 6.9, p= 0.03). Mean ARWMC was 9.43±6.5 and 8.5 ±7.89 in patients with and without triphasic waves, respectively (p= 0.5). The mortality rate was higher in the triphasic waves group (31.25 vs. 6.66% p= 0.02). Conclusions Patients with acute encephalopathy and triphasic waves had a higher degree of cerebral atrophy. This structural alteration may predispose to the appearance of triphasic waves. There was no significant difference in white matter lesion degree. The mortality of the triphasic waves group was high, so future studies are necessary to determine their prognostic value.